2020
DOI: 10.1038/s41598-020-68339-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and in silico analyses of MIF cytokine and TLR signalling interplay in the LPS inflammatory response of Ciona robusta

Abstract: The close phylogenetic relationship between Ciona robusta and vertebrates makes it a powerful model for studying innate immunity and the evolution of immune genes. To elucidate the nature and dynamics of the immune response, the molecular mechanisms by which bacterial infection is detected and translated into inflammation and how potential pattern recognition receptors (PRRs) are involved in pathogen recognition in tunicate C. robusta (formerly known as Ciona intestinalis), we applied an approach combining bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…C. robusta specimens were collected from Sciacca harbor (Sicily, Italy) and were acclimatized and maintained as reported in Arizza et al [ 33 ]…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…C. robusta specimens were collected from Sciacca harbor (Sicily, Italy) and were acclimatized and maintained as reported in Arizza et al [ 33 ]…”
Section: Methodsmentioning
confidence: 99%
“…Fragments of pharynx tissue (200 mg) were immediately soaked in RNAlater tissue collection solution (AMBION, Austin, TX, USA) and Total RNA extraction was performed as reported in in Arizza et al [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, MIF positively regulates the expression of TLR4 in macrophages promoting the recognition of LPS, a cell wall constituent of most Gram-negative bacteria, by the innate immune system [ 79 , 87 , 88 ]. A very recent report showed that Mif gene expression is activated by LPS in Ciona Robusta , a marine invertebrate model, suggesting MIF as a universal signaling mediator for the defense against pathogens [ 89 ].…”
Section: Mif In Normal and Pre-eclamptic Pregnancymentioning
confidence: 99%